2020
DOI: 10.3389/fmicb.2020.01070
|View full text |Cite
|
Sign up to set email alerts
|

A Bivalent Human Adenovirus Type 5 Vaccine Expressing the Rabies Virus Glycoprotein and Canine Distemper Virus Hemagglutinin Protein Confers Protective Immunity in Mice and Foxes

Abstract: The development of a safe and efficient multivalent vaccine has great prospects for application. Both rabies virus (RABV) and canine distemper virus (CDV) are highly infectious antigens, causing lethal diseases in domestic dogs and other carnivores worldwide. In this study, a replication-deficient human adenovirus 5 (Ad5)-vectored vaccine, rAd5-G-H, expressing RABV glycoprotein (G) and CDV hemagglutinin (H) protein was constructed. The RABV G and CDV H protein of rAd5-G-H were expressed and confirmed in infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…in Cynomolgus Macaques. The titre of RVNA ≥0.5 IU/ml in sera was considered to be sufficient for protection from rabies infections, and the RVNAs are mainly specific to its surface G protein [ 44 ]. Thus, the AAV9 was a high-efficiency vector for gene delivery of the RABV G in mice and in NHPs.…”
Section: Discussionmentioning
confidence: 99%
“…in Cynomolgus Macaques. The titre of RVNA ≥0.5 IU/ml in sera was considered to be sufficient for protection from rabies infections, and the RVNAs are mainly specific to its surface G protein [ 44 ]. Thus, the AAV9 was a high-efficiency vector for gene delivery of the RABV G in mice and in NHPs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been recent experimental vaccines produced using other vectors, such as a replication-defective human adenovirus that expresses the H protein of CDV. This experimental vaccine was shown to produce a humoral immune response in foxes (mean VN titer of 1:38 at 4 weeks post-vaccination), and provided protection against a lethal challenge four weeks after a single intramuscular injection with a very high dose (10 9 green fluorescent units of the vaccine virus) [ 86 ]. This vectored vaccine is bivalent- also expresses a protein of rabies virus, but this vaccine is missing the more conserved F protein of CDV that has been demonstrated to elicit a neutralizing response against more divergent CDV strains [ 85 ].…”
Section: Development Of a New Vaccinementioning
confidence: 99%
“…As a research hotspot in recent years, the recombinant live vector recombinant vaccine of CSF is a novel vaccine prepared by recombining the virus antigen gene into a live vector that can express exogenous virus protein, which can stimulate the body to produce a specific immune response (Wei et al, 2021). At present, the structure and function of the adenovirus genome have been studied thoroughly; meanwhile, human type 5 nonreplicating adenovirus vectors have attracted researchers' attention because of their safety, wide host range and stability (Zhu et al, 2017;Yan et al, 2020). Previous studies have shown that adenovirus vectors can induce strong specific cellular and humoral immune responses, which are widely used in the construction of new vaccines against severe zoonotic diseases (Gabitzsch et al, 2011;Lapuente et al, 2018;Zhang et al, 2018).…”
Section: A B Cmentioning
confidence: 99%
“…In addition, human replication-deficient adenovirus type 5 live vector CSF vaccine and chimeric CSFV vaccine can induce complete immune protection. Adenovirus vector vaccines have been the mainstream research direction of CSF vaccines, due to the replication deficiency of adenovirus vectors, providing double effects with the safety of inactivated vaccines and the efficacy of live vaccines (Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%